Impact of detector selections on inter‐institutional variability of flattening filter‐free beam data for TrueBeam™ linear accelerators. Issue 1 (18th November 2019) - Tanaka, Yoshihiro; Akino, Yuichi; Mizuno, Hirokazu; Isono, Masaru; Masai, Norihisa; Yamamoto, Toshijiro
Abstract: This study evaluates the type of detector influencing the inter‐institutional variability in flattening filter‐free (FFF) beam‐specific parameters for TrueBeam™ linear accelerators (Varian Medical Systems, Palo Alto, CA, USA). Twenty‐four beam data sets, including the percent depth dose (PDD), off‐center ratio (OCR), and output factor (OPF) for modeling within the Eclipse (Varian Medical Systems) treatment planning system, were collected from 19 institutions. Although many institutions collected the data using CC13 (IBA Dosimetry, Schwarzenbruck, Germany) or PTW31010 semiflex (PTW Freiburg, Freiburg, Germany) ionization chambers, some institutions used diode detectors, diamond detectors, and ionization chambers with smaller cavities. The OCR data included penumbra width, full width at half maximum (FWHM), and FFF beam‐specific parameters, including unflatness and slope. The data measured by CC13/PTW31010 ionization chambers were compared with those measured by all other detectors. PDD data demonstrated the variations within ±1% at the dose fall‐off region deeper than peak depth. The penumbra widths of the OCR measured with the CC13/PTW31010 detectors were significantly larger than those measured with all other detectors ( P < 0.05). Especially the EDGE detector (Sun Nuclear Corp., Melbourne, FL, USA) and the microDiamond detectors (model 60019; PTW Freiburg) demonstrated much smaller penumbra values compared to those of the CC13/PTW31010 detectors for the 30 × 30 mm 2 field. There was no difference in the FWHM, unflatness, and slope parameters between the values for the CC13/PTW31010 detectors and all other detectors. OPF curves demonstrated small variations, and the relative difference from the mean value of each data point was almost within 1% for all field sizes. Although the penumbra region exhibited detector‐dependent variations, all other parameters showed tiny interunit variations regardless of the detector type.